Johann Zöllner: Fourth Dimention and Spiritual Phenomena in the end of Nineteenth Century - Ferreira, Juliana Mesquita Hidalgo (Circumscribere International Journal for the History of Science, 2008)
Towards the second half of 19th century some phenomena, then called "spiritual", became focus of discussion in the scientific community. The English chemisty William Crookes mantained that mediums were people endowed with a great development of a "psychic force" which could modify the weight of objects and put them in movement. The fourth dimension hypothesis was in that period taken by the German astronomer Johann Zöllner to explain some phenomena observed in the presence of mediums (slate writing, knots in strings without free ends, and other effects) as results of action practiced by four-dimensional beings. The aims of this work are to understand how the fourth dimensional concept was articulated (with spatial meaning) in the context of investigations about spiritual phenomena and how those inquiries were received by the scientific community in that period.